DEVELOPMENT OF INTERACTIVE ANIMATED VIDEO LEARNING MEDIA ON ENERGY TRANSFORMATION MATERIAL FOR CLASS IV PRIMARY SCHOOL - Afina, Nazzila Hasya; Irianto, Dede Margo; Aljamaliah, Syifa Nailul (PROGRES PENDIDIKAN, 2024)
This research is based on the use of animated video learning media which has often been one-way between the media and students without actively involving students. This research was conducted to describe the initial design, results of design development, as well as user responses to interactive animated video learning media on energy transformation material. Interactive animated video learning media was developed using the Design and Development (D&D) research method and using the ADDIE research model which includes five stages, namely analysis, design, development, implementation, and evaluation. The results of the assessment of the interactive animated video learning media that have been developed are obtained from validation questionnaire scores by material experts of 88.89% in the "very feasible" category, media experts of 91.1% in the "very feasible" category, language experts of 79.17 % in the "feasible" category, and the overall expert validation percentage was 86.39% in the "very feasible" category. The media that had been developed was then tested on users and obtained a percentage of 85.42% in the "very appropriate" category from responses from teachers, 87.96% in the "very appropriate" category from fourth grade elementary school students, and user response assessment overall 86.69% in the "very feasible" category. Based on the recapitulation of the expert validator assessment results and user responses, it shows that the interactive animated video learning media that has been developed is very suitable for use in the learning process on energy transformation material for class IV elementary schools.